The role of the cerebellum in dystonia - Alexander S. Wang; Alexander S. Wang; Ibrahim M. Alkhodair; Ibrahim M. Alkhodair; Camilla W. Kilbane; Camilla W. Kilbane (Dystonia)
Dystonia is a neurologic disorder characterized by abnormal muscle contractions and postures, which is vastly heterogeneous in its etiologies and clinical manifestations. The role of the basal ganglia in the pathogenesis of dystonia is well known, however, there has been a recent surge of evidence implicating the malfunction of a wide network, including a prominent role of the cerebellum. In this review article, we explore the role of the cerebellum in generating dystonia through multiple lines of basic science and clinical evidence. Neurophysiological, radiological, and pathological findings in various dystonia syndromes implicate an important role of the cerebellum. Dystonia additionally accompanies many known ataxic cerebellar disorders such as spinocerebellar ataxia. Genetic and pharmacologic mouse models of dystonia have demonstrated various degrees of cerebellar pathophysiology. There is emerging evidence supporting cerebellar neuromodulation in the treatment of dystonia. Lastly, we describe cerebellar, cortical, and subcortical motor connections which provide a connectomic basis where the cerebellum may play either a primary or ancillary role in generating dystonia.